The Potential Impact of ChatGPT on Education: Using History as a Rearview Mirror - Mengqian Wang (王梦倩); Wenge Guo (郭文革) (ECNU Review of Education)
Highlights This review compares generative artificial intelligence with five representative educational technologies in history and concludes that AI technology can become a knowledge producer and thus can be utilized as educative AI to enhance teaching and learning outcomes. From a historical perspective, each technological breakthrough has affected education by changing how symbols are represented and how knowledge is carried. The emergence of new educational technology is always accompanied by doubt, vigilance, and rejection from the traditional community. The new educational technology, generative artificial intelligence, interacts with the old, creating an increasingly complex ecology of educational technology. Three suggestions are proposed for adjusting the education system: first, promoting small-scale, individualized, and conversational teaching in schools; second, developing teachers’ and students’ digital literacy in a multi-curricula system; and third, conducting research on grading and classification standards for the application of AI in education.